Petrologi - geokimia batuan Gunung Api Tampomas dan sekitarnya - Dirk, Mesker H. (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no1.20083Volcanic rocks of Mount Tampomas and its surroundings belong to low–K, calc–alkaline, and high–K series of basalt, basaltic andesite, and andesite suites containing 48.59 – 60.49 wt% of SiO and 0.31-1.67 wt% of K O. The rocks are typically formed in an island arc environment characterized by the high content of Al O (16.47 – 21.76 wt%), low to moderate content of MgO (2.37 – 8.84 wt%), low content of both titanium TiO (< 1 wt%) and high field strength elements (HFSEs), negative anomaly of Nb relative to K and La. The light rare earth elements (LREEs) enrichment but low abundances of heavy rare earth elements (HREEs) indicate fractionation process. The parent magma was an extensive removal of olivine and clino-pyroxene, plagioclase, apatite, and titanoferrousmagnetite from a basalt olivine magma of N-MORB character that was firstly enriched by LILEs such as Ba, Rb, Th, K, and LREE (La). The differentiation lasted, and the magma became water undersaturated at the crystallization phase of hornblende. The high content of incompatible elements such as Ba, Th, La, Ce, may indicate contamination by liquid derived from the subducted slab.